Pendampingan Membaca Al-Qur’an bagi Majelis Taklim Annisa Persit Kota Jayapura – Papua - Amri, Amri; Al Abza, M. Thohar (Penerbit Goodwood, 2024)
Purpose: This assistance is based on the presence of mothers in a community of the Taklim Council in reading the Qur'an is still not fluent. So that the implementation of this assistance will be addressed to the Mothers of the Annisa Persit Taklim Council in Jayapura City Methodology: Assistance in community service activities was carried out using planning, training, and mentoring methods. So that the method will produce changes Results: The results of this community service activity show that the implementation of the Quran recitation assistance program for the Mothers of the Annisa Persit Taklim Council went smoothly from the networking stage to its implementation.For example, the enthusiasm of mothers to participate in activities, then the teaching and learning process carried out, to assistance as well as practice in reading and reciting the Quran. Furthermore, judging from the success of the ability, it can be seen the seriousness of mothers to participate in this activity so that there can be seen developments in reading and reciting the Quran, even though it is not significant for participants who follow it. Limitations: A limitation of this activity is that its implementation is not sustainable. The limitations of participants in participating in mentoring activities to read the Quran. Contribution: Contribution to this activity is to help Muslims properly and correctly read the Quran. Thus, someone who wants to learn Islam is not only in one particular field but as a whole. This activity also helps mothers who still lack knowledge about the rules in reading the Quran to change their understanding.